Software Bug Detection Causes a Shift From Bottom-Up to Top-Down Effective Connectivity Involving the Insula Within the Error-Monitoring Network - Castelhano, Joao; Duarte, Isabel C.; Couceiro, Ricardo; Medeiros, Julio; Duraes, Joao; Afonso, Sónia; Madeira, Henrique; Castelo-Branco, Miguel (Frontiers in Human Neuroscience, 2022)
The neural correlates of Software programming skills have been the target of an increasing number of studies in the last few years. Those studies focused on error monitoring during software code inspection. Others have studied task-related cognitive load as measured by distinct neurophysiological measures. Most studies addressed only syntax errors (shallow level of code monitoring). However, one recent fMRI study suggested a pivotal role of the insula during error monitoring when challenging deep level analysis of code inspection was required. This raised the hypothesis that the insula is causally involved in deep error monitoring. To confirm this hypothesis, we carried out a new fMRI study where participants performed a deep source-code comprehension task that included error monitoring to detect bugs in the code. The generality of our paradigm was enhanced by comparison with a variety of tasks related to text reading and bugless source-code understanding. Healthy adult programmers (N=21) participated in this 3T fMRI experiment. The activation maps evoked by error related events confirmed significant activations in the insula (Pbonferroni<0.05). Importantly, a posterior to anterior causality shift was observed concerning the role of the insula: in the absence of error causal directions were mainly bottom-up, whereas upon their presence strong causal top-down effects from frontal regions, and in particular the anterior cingulate cortex was observed.